Overexpression of CDCA8 Predicts Poor Prognosis and Promotes Tumor Cell Growth in Prostate Cancer - Wan, Shun; He, Yang; Zhang, Bin; Yang, Zhi; Du, Fang-Ming; Zhang, Chun-Peng; Fu, Yu-Qiang; Mi, Jun (Frontiers in Oncology, 2022)
Human cell division cycle-related protein 8 (CDCA8) is an essential component of the vertebrate chromosomal passenger complex (CPC). CDCA8 was confirmed to play a role in promoting malignant tumor progression. However, the exact function of CDCA8 in the development and progression of prostate cancer (PCa) remains unclear. In this study, the database GSE69223 was downloaded by the gene expression omnibus (GEO) database, as well as CDCA8 expression differences in multiple tumor tissues and normal tissues were detected by The Cancer Genome Atlas (TCGA), TIMER, Oncomine, and Ualcan databases. Kaplan-Meier and Cox regression methods were used to analyze the correlation between CDCA8 expression and prognosis in PCa. We confirmed the expression of CDCA8 in PCa tissues by HPA. We also analyzed the association of CDCA8 expression with PCa clinical characteristics in the TCGA database. To further understand the role of CDCA8 in PCa, we assessed the effects of CDCA8 on PCa cell growth, proliferation, and migration in vitro studies. As a result, CDCA8 was significantly overexpressed in PCa cells compared with normal prostate cells. High CDCA8 expression predicts poor prognosis in PCa patients, and CDCA8 expression was higher in high-grade PCa. In addition, silencing of CDCA8 significantly inhibited PCa cell proliferation and migration. In summary, CDCA8 promoted the proliferation and migration of PCa cells.